Pengaruh Disiplin Kerja, Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan di PT Sentra Agroprima Lestari - Romadhona, Anna Bella Claudia; Iristian, Jovi; Adistie, Gisti Riza (Faculty of Islamic Economics and Business, Madura Islamic State University, 2024)
The purpose of this research is to examine how the influence of the work environment and work discipline on employee performance. Employees of PT Sentra Agroprima Lestari Surabaya became the research subjects. This study uses quantitative research methods as its methodology. This type of research uses a quantitative approach and uses primary data. The population of the research was 35 employees of PT Sentra Agroprima Lestari Surabaya. The sampling technique in this research uses saturated samples, namely a sampling technique that uses all members of the population as samples. Data collection through questionnaires. The analysis method used is the Statistical Product and Service Solution (SPSS) method. Keywords: Work Discipline, work motivation, work environment and performance